Microbial communities in submarine permafrost and their response to permafrost degradation and warming - Mitzscherling, Julia (Dr.) (2020)
The Arctic region is especially impacted by global warming as temperatures in high latitude regions have increased and are predicted to further rise at levels above the global average. This is crucial to Arctic soils and the shallow shelves of the Arctic Ocean as they are underlain by permafrost. Perennially frozen ground is a habitat for a large number and great diversity of viable microorganisms, which can remain active even under freezing conditions. Warming and thawing of permafrost makes trapped soil organic carbon more accessible to microorganisms. They can transform it to the greenhouse gases carbon dioxide, methane and nitrous oxide. On the other hand, it is assumed that thawing of the frozen ground stimulates microbial activity and carbon turnover. This can lead to a positive feedback loop of warming and greenhouse gas release. Submarine permafrost covers most areas of the Siberian Arctic Shelf and contains a large though unquantified carbon pool. However, submarine permafrost is not only affected by changes in the thermal regime but by drastic changes in the geochemical composition as it formed under terrestrial conditions and was inundated by Holocene sea level rise and coastal erosion. Seawater infiltration into permafrost sediments resulted in an increase of the pore water salinity and, thus, in thawing of permafrost in the upper sediment layers even at subzero temperatures. The permafrost below, which was not affected by seawater, remained ice-bonded, but warmed through seawater heat fluxes. The objective of this thesis was to study microbial communities in submarine permafrost with a focus on their response to seawater influence and long-term warming using a combined approach of molecular biological and physicochemical analyses. The microbial abundance, community composition and structure as well as the diversity were investigated in drill cores from two locations in the Laptev Sea, which were subjected to submarine conditions for centuries to millennia. The microbial abundance was measured ...